Sarilumab is not Inferior to Tocilizumab in the Treatment of Cytokine Release Syndrome in COVID-19 - V. T. Ivashkin; R. V. Maslennikov; E. V. Vasilieva; M. L. Chipurik; P. A. Semikova; V. V. Semenets; T. A. Russkova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Objective. Cytokine release syndrome (CRS) is a dangerous complication of the new coronavirus infection (COVID-19). The study aimed to compare sarilumab (SAR group) with tocilizumab (TOC group) and patients without anticytokine treatment (CON group) in treatment of CRS in COVID-19.Methods. The retrospective real life study included COVID-19 patients with C-reactive protein(CRP)  level >60 mg/l.Results. We enrolled 24 patients in SAR group, 27 patients in TOC group and 47 patients in CON group. Mortality was lower in SAR and TOC groups than in CON group (12.5% and 14.8% vs. 31.9%; p=0.021 and p=0.031) with no difference between SAR and TOC groups (p=0.389).  SAR patients unlike TOC patients required intensive care unit admission less frequently then CON patients (16.7% and 25.9% vs. 46.3%; p=0.013 and p=0.077). An increase in oxygen saturation was observed in SAR and TOC groups (p=0.001 and p=0.004; greater in SAR group [p=0.022]), but not in CON group (p=0.764) in 7-10 days after administration of these drugs. The decrease in CRP level was greater in  SAR and TOC groups than in CON group (p=0.016 and p<0.011), with no difference between SAR and TOC groups (p=0.236).Conclusion. Sarilumab is not inferior to tocilizumab in COVID-19